2022
DOI: 10.1186/s12905-022-01819-6
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, and practice of cervical cancer prevention and associated factors among commercial sex workers in Shashemene Town, West Arsi, Oromia Region, Ethiopia

Abstract: Background The distribution of deaths and morbidities related to cervical cancer is disproportionally higher in low- and middle-income countries. In Ethiopia, there is a limited study on cervical cancer prevalence on Sex Workers, but a study conducted in Central America risk of developing HPV infection in sex workers is 2.5 times more than the general population. But a study conducted in the general population in Ethiopia reports that the incidence and mortality due to cervical cancer in Ethiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…There were studies that reported that 2.5% (14) or none (22) of university students were screened for cervical cancer. About 20.3% of female sex workers responded that they had received cervical cancer screening (41).…”
Section: Cervical Cancer Screeningmentioning
confidence: 99%
“…There were studies that reported that 2.5% (14) or none (22) of university students were screened for cervical cancer. About 20.3% of female sex workers responded that they had received cervical cancer screening (41).…”
Section: Cervical Cancer Screeningmentioning
confidence: 99%